2012
DOI: 10.1021/ie202797s
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Process Configuration for High-Temperature Sulfur Mitigation during Biomass Conversion via Indirect Gasification

Abstract: amount of design data, more analysis should be performed for mixed alcohols synthesis to examine biomass-optimized configurations including recycle for maximum conversion and the resulting economics. All biomass fuels have potential to significantly reduce the import of petroleum products. Additionally, economies of scale can play a large factor in lowering the product cost. Therefore, opportunities to co-feed with coal or natural gas systems may be one way to get renewable fuels into the marketplace, just as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 126 publications
(256 reference statements)
0
6
0
Order By: Relevance
“…This can be advantageously incorporated into the design of biomass and other gasification-based processes in a number of ways. Byproduct CO 2 can be made available and possibly even recycled to extinction via conventional acid gas removal systems or direct recycle of CO 2 -rich gas streams from the process, and can be used for fluidization of biomass in the gasifier to reduce process steam requirements . For example, CO 2 is a byproduct from the mixed alcohol synthesis and Fischer–Tropsch reactors using iron-based catalysts because of the water-gas shift reaction.…”
Section: Resultsmentioning
confidence: 99%
“…This can be advantageously incorporated into the design of biomass and other gasification-based processes in a number of ways. Byproduct CO 2 can be made available and possibly even recycled to extinction via conventional acid gas removal systems or direct recycle of CO 2 -rich gas streams from the process, and can be used for fluidization of biomass in the gasifier to reduce process steam requirements . For example, CO 2 is a byproduct from the mixed alcohol synthesis and Fischer–Tropsch reactors using iron-based catalysts because of the water-gas shift reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, depending upon the gasifier type and gasification temperature, the syngas product may contain polyaromatic organic constituents called “tars” that can condense and polymerize downstream, affecting unit operations and/or catalysts (Table ). A warm syngas cleanup process that uses solid sorbents as well as catalysts for the removal of the various harmful contaminants, especially but not limited to sulfur gases, would eliminate this significant thermal inefficiency …”
Section: Introductionmentioning
confidence: 99%
“…2 A warm syngas cleanup process that uses solid sorbents as well as catalysts for the removal of the various harmful contaminants, especially but not limited to sulfur gases, would eliminate this significant thermal inefficiency. 3 Syngas from coal can contain as much as 3 wt % sulfur (mainly as H 2 S), whereas the concentration of sulfur in the gasification product from most biomass feedstocks is typically much less and on the order of 100 ppm (Table 1). 2 To protect downstream catalysts, it has been reported that the sulfur concentration must be reduced to less than 50 ppb.…”
Section: Introductionmentioning
confidence: 99%
“…It can greatly enhance the power generation efficiency and lower the pollutant emissions causing environmental pollution [1][2][3]. In an IGCC power plant, hot coal gas containing amounts of sulfur compounds is first purified and then introduced into gas turbines for generating electricity.…”
Section: Introductionmentioning
confidence: 99%